SOME LOCULOASCOMYCETES FROM MAHARASHTRA (INDIA) (GENUS: BOTRYOSPHAERIA) - RAMESH, C.H (Indian Phytopathology, 2002)
Six species of Loculoascomycetes, viz, Botryosphaeria aiibagensis, B. arctostaphyii, B. berengeriana, B. festucae, B. purandharensis and B. uisci are described and illustrated. Botryosphaeria aiibagensis and B. purandharensis are new to science and the rest are new to India